Disparities in Peripheral Artery Disease Hospitalizations Identified Among Understudied Race-Ethnicity Groups - Chen, LaiTe; Zhang, Donglan; Shi, Lu; Kalbaugh, Corey A. (Frontiers in Cardiovascular Medicine, 2021)
Background: To assess racial/ethnic differences in disease severity, hospital outcomes, length of stay and healthcare costs among hospitalized patients with peripheral artery disease (PAD). Methods: This study used data from the National Inpatient Sample (NIS) to explore the racial/ethnic disparities in PAD-related hospitalizations including presence of PAD with chronic limb threatened ischemia (CLI), amputation, in-hospital mortality, length of hospital stays and estimated medical costs. Race-ethnicity groups included non-Hispanic White, Black, Hispanic, Asian or Pacific Islander, Native American, and others (multiple races). Regression analyses adjusted for age, gender, Charlson Comorbidity Index, primary payer, patient location, bed size of the admission hospital, geographic region of the hospital, and rural/urban location of the hospital. Results: A total of 341,480 PAD hospitalizations were identified. Compared with non-Hispanic Whites, Native Americans had the highest odds of PAD with CLI (OR=1.77, 95% CI: 1.61, 1.95); Black (OR=1.71, 95% CI: 1.66, 1.76) and Hispanic (OR=1.36, 95% CI: 1.31,1.41) patients had higher odds of amputation; Asian or Pacific Islanders had a higher mortality (OR=1.20, 95% CI: 1.01,1.43), whereas Black (OR=0.81, 95% CI: 0.76, 0.87) patients has a lower mortality; Asian or Pacific Islanders incurred higher overall inpatient costs (Margin=30093.01, 95% CI: 28827.55, 31358.48) and most prolonged length of stay (IRR= 0.14, 95% CI: 0.09, 0.18). Conclusions: Our study identified elevated odds of amputation among Hispanic patients hospitalized with PAD as well as higher hospital mortality and medical expenses among Asian or Pacific Islander PAD inpatients. These two demographic groups were previously thought to have a lower risk for PAD and represent important populations for further investigation.